2002
DOI: 10.1038/sj.mp.4001152
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel variant of the human NR2B gene promoter region and its possible association with schizophrenia

Abstract: N-methyl-D-aspartate (NMDA) receptor dysfunction is involved in the pathogenesis of schizophrenia. We determined the nucleotide sequence of the 5′-upstream region of the human NMDA receptor 2B (NR2B) subunit gene and identified a novel T-200G variant located in one of the Sp1 binding sites. To investigate the effect of this variant on the transcriptional activity of the hNR2B gene, we performed gene reporter assays using PC12 pheochromocytoma cells transiently transfected with luciferase reporter plasmids. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 31 publications
1
48
2
Order By: Relevance
“…44 An overlap in genetic susceptibility for schizophrenia and BPI has been argued by many investigators and was recently reviewed by Craddock et al 45 We agree that there is strong evidence for an overlap of genetic factors contributing to these two phenotypes, and we recently published a candidate gene association study 17 that investigated 440 SNPs in 64 functional and positional candidates for both disorders, genotyped in two sets of triads of AJ descent ascertained for either BPI or schizophrenia. Although at that time studies had suggested GRIN2B only as a candidate for schizophrenia, 40,41 in our study, it was among the best findings for BPI. More recently, a study by Martucci et al 23 also detected an association between GRIN2B DNA variants and both BP and schizophrenia, and a metaanalysis supported the association with schizophrenia.…”
Section: Discussionmentioning
confidence: 63%
“…44 An overlap in genetic susceptibility for schizophrenia and BPI has been argued by many investigators and was recently reviewed by Craddock et al 45 We agree that there is strong evidence for an overlap of genetic factors contributing to these two phenotypes, and we recently published a candidate gene association study 17 that investigated 440 SNPs in 64 functional and positional candidates for both disorders, genotyped in two sets of triads of AJ descent ascertained for either BPI or schizophrenia. Although at that time studies had suggested GRIN2B only as a candidate for schizophrenia, 40,41 in our study, it was among the best findings for BPI. More recently, a study by Martucci et al 23 also detected an association between GRIN2B DNA variants and both BP and schizophrenia, and a metaanalysis supported the association with schizophrenia.…”
Section: Discussionmentioning
confidence: 63%
“…However, in molecular-genetic studies, the functionality of only the -200T/G polymorphism has been described. This variant was found to be localized in the putative Sp1 binding site in the 5'-upstream region of the GRIN2B gene, and different luciferase reporter activity was found for different alleles, suggesting that this region is crucial for GRIN2B regulation [11]. For the other two polymorphisms, there are no experimental data on their importance in gene regulation; however, such influence cannot be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…The three GRIN2B polymorphisms, 366C/G (Pro122) (rs7301328), rs890G/T and -200T/G (rs1019358), were analyzed by PCR-RFLP analysis according to Ohtsuki et al [13], with minor modifications. The SNP selection was based on the functionality of the -200G/T polymorphism [9,11] and the fact that the other two polymorphisms (rs7301328 and rs890) showed positive association with schizophrenia [1,13], which may have some common genetic background with bipolar disorder.…”
Section: Subjectsmentioning
confidence: 99%
“…16,22,23 Miyatake et al have observed that the T allele of the GRIN2B rs1019385 SNP results in increased luciferase transporter activity in the presence of nerve growth factor (NGF). 24 The presence of a G allele had no effect on reporter activity, suggesting that GRIN2B rs1019385 may have a role in transcriptional control of the GRIN2B transcript. 24 The G72 gene product, D-amino-acid oxidase activator (DAOA), activates the peroxisomal protein D-amino-acid oxidase (DAO).…”
Section: Introductionmentioning
confidence: 99%
“…24 The presence of a G allele had no effect on reporter activity, suggesting that GRIN2B rs1019385 may have a role in transcriptional control of the GRIN2B transcript. 24 The G72 gene product, D-amino-acid oxidase activator (DAOA), activates the peroxisomal protein D-amino-acid oxidase (DAO). 25 This protein (G30) degrades D-serine, which acts, similar to glycine, as a coactivator on the "glycine binding site" of the glutamatergic NMDA receptor.…”
Section: Introductionmentioning
confidence: 99%